Comprehensive Evaluation of Rhythm Monitoring Strategies in Screening for Atrial Fibrillation: Insights From Patients at Risk Monitored Long Term With an Implantable Loop Recorder - Diederichsen, Søren Zöga; Haugan, Ketil Jørgen; Kronborg, Christian; Graff, Claus; Højberg, Søren; Køber, Lars; Krieger, Derk; Holst, Anders Gaarsdal; Nielsen, Jonas Bille; Brandes, Axel; Svendsen, Jesper Hastrup (Circulation (New York, N.Y.), 2020)
Stroke is an increasing health problem worldwide. Atrial fibrillation (AF) is a major risk factor for stroke, and the attention given to AF screening is rising, as new monitoring technologies emerge. We aimed to evaluate the performance of a large panel of screening strategies and to assess population characteristics associated with diagnostic yield. Individuals with stroke risk factors but without AF were recruited from the general population to undergo screening with an implantable loop recorder. New-onset AF lasting ≥6 minutes was adjudicated by senior cardiologists. After continuous monitoring for >3 years, complete day-to-day heart rhythm data sets were reconstructed for every participant, including exact time of onset and termination of all AF episodes. Random sampling was applied to assess the sensitivity and negative predictive value of screening with various simulated screening strategies compared with the implantable loop recorder. The diagnostic yield across strategies and population subgroups was compared by use of nonparametric tests. The rhythm data sets comprised 590 participants enduring a total of 659 758 days of continuous monitoring and 20 110 AF episodes. In these data, a single 10-second ECG yielded a sensitivity (and negative predictive value) of 1.5% (66%) for AF detection, increasing to 8.3% (67%) for twice-daily 30-second ECGs during 14 days and to 11% (68%), 13% (68%), 15% (69%), 21% (70%), and 34% (74%) for a single 24-hour, 48-hour, 72-hour, 7-day, or 30-day continuous monitoring, respectively. AF detection further improved when subsequent screenings were performed or when the same monitoring duration was spread over several periods compared with a single period (eg, three 24-hour monitorings versus one 72-hour monitoring; <0.0001 for all comparisons). The sensitivity was consistently higher among participants with age ≥75 years, male sex, CHADS score >2, or NT-proBNP (N-terminal pro-B-type natriuretic peptide) ≥40 pmol/L and among participants with underlying ≥24-hour AF episodes compared with shorter AF ( <0.0001 for all screening strategies). In screening for AF among participants with stroke risk factors, the diagnostic yield increased with duration, dispersion, and number of screenings, although all strategies had low yield compared with the implantable loop recorder. The sensitivity was higher among participants who were older, were male, or had higher NT-proBNP. Registration: URL: https://www.clinicaltrials.gov; Unique identifier: NCT02036450.